2020
DOI: 10.2337/db19-1206
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Induced Increase in Cystatin C Alleviates Tissue Inflammation

Abstract: We recently demonstrated that removal of one kidney (uninephrectomy; UniNx) in mice reduced high fat-diet (HFD)-induced adipose tissue inflammation thereby improving adipose tissue and hepatic insulin sensitivity. Of note, circulating cystatin C (CysC) levels were increased in UniNx compared to sham-operated mice. Importantly, CysC may have anti-inflammatory properties, and circulating CysC levels were reported to positively correlate with obesity in humans and as shown herein in HFD-fed mice. However, the cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…However, in our study, no relationship between eGFR and obesity was found. The present study showed that the elevated circulating cystatin C levels in study participants with obesity may be to counteract obesity-related inflammation (27). Elevated cystatin C levels in adolescence were also associated with lipid metabolic dysregulation and cardiometabolic risk (28).…”
Section: Discussionmentioning
confidence: 79%
“…However, in our study, no relationship between eGFR and obesity was found. The present study showed that the elevated circulating cystatin C levels in study participants with obesity may be to counteract obesity-related inflammation (27). Elevated cystatin C levels in adolescence were also associated with lipid metabolic dysregulation and cardiometabolic risk (28).…”
Section: Discussionmentioning
confidence: 79%
“…Creatinine-based equations may overestimate GFR when used in individuals with a BMI >30 kg/m 2 due to variable body composition, including reduced muscle mass [ 40 ]. In contrast, cystatin C synthesis has been shown to be upregulated in adipose tissue in obese individuals and to counteract inflammation of peripheral insulin-sensitive tissues [ 41 ]. Recently it has been shown that in severely obese subjects enrolled in medical weight loss programmes, cystatin C–based eGFR and indexation to actual body surface area (BSA) instead of 1.73 m 2 may provide the most accurate estimate of kidney function [ 42 ].…”
Section: Effect Of Body Compositionmentioning
confidence: 99%
“…Serum cystatin C is a cysteine protease inhibitor and has been reported to be a significant predictor to carry prognostic or diagnostic information in human diseases, including various malignant cancers. [17][18][19][20][21][22][23][24][25][26] However, a study regarding the predictive value of serum cystatin C on NPC patients treated with IMRT has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…15 Cystatin C affects protein catabolism, antigen presentation, bone resorption, and hormone processing, and it can couple to cleavage of membrane and extracellular matrix proteins during tissue remodeling irregularly, and its homeostasis imbalance can lead to disease, including cancer. 16 Previous studies have shown that serum cystatin C level plays important roles in diagnosing and predicting human diseases, such as cirrhosis, 17 inflammation, 18 Parkinson's disease, 19 kidney disease, 20 and cardiovascular disease. 21 Many studies have reported that cystatin C plays important roles in predicting the prognosis and effect of clinical therapy of various cancers, such as myeloma, 22, esophageal cancer, 23 renal carcinoma, 24 upper tract urothelial carcinoma, 25 non-Hodgkin's B-cell lymphoma, 26 and so on.…”
Section: Introductionmentioning
confidence: 99%